2009
DOI: 10.1186/1756-9966-28-116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relative dose intensity (RDI) in CHOP combined with rituximab (R-CHOP) on survival in diffuse large B-cell lymphoma

Abstract: BackgroundRecently, maintaining higher relative dose intensity (RDI) of chemotherapeutic drugs has become a widespread practice in an attempt to achieve better outcomes in the treatment of aggressive lymphoma. The addition of rituximab to chemotherapy regimens has significantly improved outcome in diffuse large B-cell lymphoma (DLBL). However, it is unknown if higher RDI in chemotherapy when combined with rituximab leads to a better outcome in aggressive B-cell lymphoma.MethodsWe retrospectively evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 20 publications
1
49
1
1
Order By: Relevance
“…Hirakawa et al reported the OS at 2 years to be significantly higher in patients in whom the ARDI was maintained at 70% or more, while the PFS at 2 years tended to be higher in patients in whom the ARDI was maintained at 70% or more [21], while in our study DFS was not affected by DI and RDI of doxorubicin (p = 0.35) or cyclophosphamide (p = 0.386). Terada et al retrospectively evaluated the impact of the RDI of initial R-CHOP on outcome in newly diagnosed DLBCL patients and reported that mortality was affected by RDI of R-CHOP as the initial treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hirakawa et al reported the OS at 2 years to be significantly higher in patients in whom the ARDI was maintained at 70% or more, while the PFS at 2 years tended to be higher in patients in whom the ARDI was maintained at 70% or more [21], while in our study DFS was not affected by DI and RDI of doxorubicin (p = 0.35) or cyclophosphamide (p = 0.386). Terada et al retrospectively evaluated the impact of the RDI of initial R-CHOP on outcome in newly diagnosed DLBCL patients and reported that mortality was affected by RDI of R-CHOP as the initial treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…The relative dose intensity (RDI) was calculated by averaging the relative total dose intensities of the 3 agents over all treatment courses. 23 …”
Section: Response Assessmentmentioning
confidence: 99%
“…10 Since the introduction of rituximab, four independent studies, including our own, 11 have described similar findings with 10-30% of reduced RDI resulting in decreased PFS and OS in DLBCL patients. [11][12][13][14] Impact of dose intensity on outcome of fludarabine, cyclophosphamide, and rituximab regimen given in the first-line therapy for chronic lymphocytic leukemia to note that all these studies are retrospective and focused on patients treated outside the setting of clinical trials. However, very little is known about the impact of RDI in indolent lymphomas, including CLL.…”
Section: Introductionmentioning
confidence: 99%